Pengembangan Media Pembelajaran Berbasis Scratch pada Materi Perkalian Sekolah Dasar - Rila Yulastari; Refiona Andika; Fadila Suciana; Yullys Helsa (STKIP Subang, 2025)
Elementary School. The method used is Research and Development (R&D) with the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Implementation was carried out with a limited trial. The subjects of the limited trial were fourth-grade students of SDN 48 Payakumbuh. The validity of the media was tested by material experts, language experts, and media experts with percentage results of 82%, 100%, and 86%, respectively, all of which are included in the